LITERASI DIGITAL DALAM MENGATASI INFODEMI PADA ERA NEW NORMAL - Muhammad Isa Yusaputra; Israwaty Suriady; Giska Mala Rahmarini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
This article is based on disinformation about Covid-19 appearing in various topics related to hoax news because the messages conveyed are very exaggerated and sometimes untrue. Hoaxes regarding health need to be combated by increasing literacy during this Covid-19 pandemic. This study aims to provide an overview of the circulation of hoax information about health in preventing COVID-19 in digital media and to find out digital literacy in overcoming the infodemic in the new normal era. Using qualitative methods, this study aims to determine the circulation of hokas information about health in preventing Covid-19 in digital media and to determine digital literacy in overcoming the infodemic in the new normal era. The results of the study found four factors that affect digital literacy.